Price Discrimination Under the Robinson-Patman Act (Book). - Zeff, Stephen A.; Taggart, Herbert F. (The Accounting Review, 1963)
Reviews the book "Price Discrimination Under the Robinson-Patman Act," by Frederick M. Rowe.